Pop-up book media integrated Islamic values and Pancasila to foster motivation and care - Muzayanati, Apriliyanti; Nugraheni, Aninditya Sri (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2023)
This study aims to motivate students in learning and instill an attitude of environmental care integrated with Islamic values and Pancasila. The research and Development (R&D) method used the ADDIE model, a type of research method pre-experimental design (nondesign) one group pretest-postest with non-parametric. The subjects of the study were 21 fourth grade students of MIN 4 Madiun. Data collection techniques consisted of observations, interviews, documentation, and questionnaires. The data then analyzed quantitatively. The results shows that first, a product has been produced with an ADDIE development model in the form of a Pop-up book Media integrated with Islam and Pancasila values. Second, eligibility results have been obtained from several experts, including material experts, got an average of 95.5%, and language validation scores obtained 88.6%. Media validation received a score of 95.4%, teacher response 88.3%, and student response to media got a score of 95.8%. So it can be concluded that this Pop-up book media is worth using. Third, there is a positive influence on students after using Pop-up book media.